2006
DOI: 10.1021/ma060004+
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ordered Nanostructures in Epoxy Thermosets:  A Mechanism of Reaction-Induced Microphase Separation

Abstract: A polystyrene-b-poly(ethylene oxide) (PS-b-PEO) diblock copolymer was synthesized via the atom transfer radical polymerization (ATRP) of styrene with mono-2-bromoisobutyryl-terminated PEO [PEO-OOCCBr(CH 3 ) 2 ] as a macroinitiator, and the polymerization was mediated by copper(I) bromide (CuBr) and 2,2′-bipyridine (BPY). The PS-b-PEO diblock copolymer was used to incorporate into epoxy resin to afford the nanostructured epoxy thermosets. Both atomic force microscopy (AFM) and small-angle X-ray scattering (SAXS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
169
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(184 citation statements)
references
References 47 publications
4
169
1
Order By: Relevance
“…In other words, the nanostructures were pre-formed before the curing reaction of the blends, and were fixed by the network formation after the curing. On the other hand, Zheng and coworkers [31][32][33][34] showed that the nanostructures of the epoxy/BCP blends can be also generated via the 'reaction-induced phase separation'. In this case, it is not required that BCPs generate the nanostructures in self-assembly prior to the curing reaction; all the BCPs may be miscible with the thermoset precursors [34].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the nanostructures were pre-formed before the curing reaction of the blends, and were fixed by the network formation after the curing. On the other hand, Zheng and coworkers [31][32][33][34] showed that the nanostructures of the epoxy/BCP blends can be also generated via the 'reaction-induced phase separation'. In this case, it is not required that BCPs generate the nanostructures in self-assembly prior to the curing reaction; all the BCPs may be miscible with the thermoset precursors [34].…”
Section: Introductionmentioning
confidence: 99%
“…The nanostructuration of the BCP in the epoxy matrix requires an immiscible block, either initially [20,21] or during polymerization [22,23], and another block that keeps its miscibility up to high or full conversions. The latter is a necessary condition to avoid macrophase separation.…”
Section: Introductionmentioning
confidence: 99%
“…In other systems, the epoxy prepolymer and the block copolymer can provide a homogeneous solution before curing, but during the curing process the nanostructure can form through a mechanism called reaction-induced microphase separation [9]. Some examples of the copolymers that give rise to nanoscopic structures include diblocks and/or triblocks of poly(ethylene oxide) with polycaprolactone (PEO-b-PCL) [9], poly(propylene oxide) (PEO-b-PPO) [10][11][12][13][14][15], poly(hexylene oxide) (PEO-b-PHO) [16], poly(n-butylene oxide) (PBO-b-PEO) [17], poly(ethyl ethylene) (PEO-b-PEE) [7,8], poly(ethylene-alt-propylene) (PEO-b-PEP) [7,8,[18][19][20][21], low molar mass polyethylene (PEO-b-PE) [22], polystyrene (PEO-b-PS) [23], and polydimethylsiloxane (PEO-b-PDMS) [24]; block copolymers of polycaprolactone with polydimethyl-siloxane (PCL-b-PDMS-b-PCL) [25,26], poly(n-butyl acrylate) (PCL-b-PBA) [27], polybutadiene(PCLb-PBD-b-PCL) [28], polystyrene (PCL-b-PS) [29], or poly(butadiene-co-acrylonitrile) (PCL-b-PBN-b-PCL) [30]; block copolymers of poly(methyl methacrylate) with polystyrene (PMMA-b-PS) [31,32], and ABC-type triblock copolymer composed of polystyrene-b-polybutadiene-b-poly(methyl methacrylate) (PS-b-PBD-b-PMMA) [33,34], and polydimethyl-siloxane-b-polycaprolactone-b-polystyrene (PDMS-b-PCL-b-PS) [35]. The formation of ordered nanostructures in these epoxy networks occurs because the PCL, PEO or PMMA block segments in these corresponding copolymers remain miscible with the epoxy matrix after curing, whereas the other immiscible block components separate out.…”
Section: Introductionmentioning
confidence: 99%